Evaluation of the Application of the Green Campus Concept at Universitas Budi Luhur Based on UI Greenmetric Category - Hakim, Hakim; Endangsih, Tri (RSF Conference Series: Engineering and Technology, 2021)
The green campus concept begins with the awareness of the academic community about the importance of various environmentally-friendly activities to support a sustainable campus. A sustainable campus is expected to be able to withstand change without harming the future academic community and the people living around the campus. This study aims to determine the application of the green campus concept at Universitas Budi Luhur with qualitative research methods through a rationalistic approach. For data processing used scoring method and mixed research methods. Universitas Budi Luhur registered itself as a participant in the Green Campus ranking program coordinated by the UI GreenMetric Team in 2019. In this study, the data processed was data from ranking results whose scores were announced in 2019 and 2020. The results of scoring in 2020 Universitas Budi Luhur earned a total of 5,850 points and was ranked 355th in the world level. The standard category of campus arrangement and infrastructure, the fulfillment of renewable energy, the absence of recycled water treatment efforts, and the use of water-saving devices have not been maximized, causing the percentage of assessment to be below. With the results of the 2020 ranking, it is hoped that it will be a spirit for a better future and there is a need for commitment from the management in determining policies related to the green campus program for campus sustainability.